2022
DOI: 10.1007/s00784-021-04356-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of malocclusion on jaw motor function and chewing in children: a systematic review

Abstract: Objective To investigate the effects of dental/skeletal malocclusion and orthodontic treatment on four main objective parameters of chewing and jaw function (maximum occlusal bite force [MOBF], masticatory muscle electromyography [EMG], jaw kinematics, and chewing efficiency/performance) in healthy children. Materials and methods Systematic searches were conducted in MEDLINE (OVID), Embase, and the Web of Science Core Collection. Studies that examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 89 publications
(401 reference statements)
0
16
1
Order By: Relevance
“…Angle Class I, Class II individuals and deepbite groups have similar chewing patterns, while crossbite groups have reverse chewing patterns [15].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Angle Class I, Class II individuals and deepbite groups have similar chewing patterns, while crossbite groups have reverse chewing patterns [15].…”
Section: Discussionmentioning
confidence: 96%
“…A longer occlusion time (ideal occlusion time is desired to be < 0.2 s) indicates the presence of premature contact during closure and negatively affects occlusal stability [11,15]. In contrast, Quadeer et al [6].have stated that the average occlusion time was 0.38 seconds in individuals who underwent orthodontic treatment and 0.41 seconds in individuals who did not undergo orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that having PCS is mostly due to left-right differences in occlusal force and masticatory efficiency [ 15 , 17 ] and does not affect the jaw and TMJ function [ 21 ]; however, it is still controversial. Orthodontic treatment not only changes the teeth alignment but also improves occlusal conditions and facilitates masticatory function in terms of jaw movement and masticatory muscle activity [ 22 , 23 ]. For example, it can change the masticatory path of a patient with unilateral mastication due to crossbite from reverse to a normal pattern to achieve bilateral mastication [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malocclusion is one of the most common dental problems that has an increasing prevalence (1)(2)(3)(4)(5)(6)(7) It may cause many ailing effects such as poor esthetics, functional limitations, speech defects as well as increase in the prevalence of dental caries and periodontal disease (8)(9)(10)(11)(12)(13) . Occlusion has also a significant influence on how individuals perceive and evaluate other individuals (14,15) .…”
Section: Introductionmentioning
confidence: 99%